2019
DOI: 10.3390/sym11111328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese on Co–Mn/CNT Bimetallic Catalyst Performance in Fischer–Tropsch Reaction

Abstract: Cobalt (Co) catalyst is supported by carbon nanotubes (CNT) using a strong electrostatic adsorption (SEA) method. To promote activity and selectivity as well as find the optimum loading percentage and its effect on catalyst performance, manganese (Mn) has been added to the Co/CNT catalyst. Samples were characterized by a scanning electron microscope (SEM-EDX), transmission electron microscope (TEM), hydrogen temperature programmed reduction (H 2 -TPR), Zeta potential, Brunauer-Emmett-Teller (BET) analysis, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…The reducibility of the catalysts was studied by temperature-programmed reduction. Figure S10 shows °C), which fits well with the data reported in the literature (220-280 °C) [32,33]. The lower reduction temperature observed for the first peak of the ex-nitrate catalysts could be explained by a confinement effect [22,34].…”
Section: Cobalt Particle Size Confinement Crystallographic Phase and Compositionsupporting
confidence: 89%
“…The reducibility of the catalysts was studied by temperature-programmed reduction. Figure S10 shows °C), which fits well with the data reported in the literature (220-280 °C) [32,33]. The lower reduction temperature observed for the first peak of the ex-nitrate catalysts could be explained by a confinement effect [22,34].…”
Section: Cobalt Particle Size Confinement Crystallographic Phase and Compositionsupporting
confidence: 89%
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 69%
“…Carbon mass balance was calculated from the moles of carbon entering the reactor relative to the moles of carbonaceous products formed. The advantage and novelty of the current studies were performed by the SEA method for synthesizing Co-Mn catalysts on CNT support for Fischer-Tropsch (FT) reaction, which has not been reported previously [26][27][28][29]. A high percentage of CO conversion and C 5+ selectivity was obtained in the present investigation.…”
Section: Process Results Dissectionmentioning
confidence: 73%
“…This work is continuation of the same project which is previously investigated and published. In the previous studies X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), X-ray Photoelectron Spectroscopy (XPS), etc characterization preformed and discussed [14][15][16][17]. Characterization techniques performed for FTS catalysts include Transmission electron microscopy (TEM) analysis on a Zeiss LIBRA 200 FE TEM at 200 kV accelerating voltage.…”
Section: Catalyst Characterization and Equationsmentioning
confidence: 99%
“…This work is a continuation of the same project which has previously been investigated and published. Previous works focused on catalyst preparation variables such as effects of catalyst active site confinement in CNT channels, addition of Mn to Co/CNT catalyst, acid and thermal treatment of CNT support, catalyst pH, percentage of Cobalt catalyst loading, calcination condition and catalyst particle size [14][15][16][17]. The present study aims to prepare a CNT-supported cobalt manganese bimetallic catalyst using the SEA method and focus on the study of the effect of Fischer-Tropsch reaction parameters such as pressure, H2/CO ratio, and reduction conditions on the performance of Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionmentioning
confidence: 99%